Post-kerion Localized sterile folliculitis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
Sterile pustules can be observed in the child. In some cases the pustules are part of a disease with known etiology as pustular psoriasis or rosacea. In other cases they are part of classical clinical pictures of unknown etiology such as neonatal toxic erythema and transient pustular melanosis, infantile acropustulosis and eosinophilic folliculitis. Sometimes, we see in the child sterile folliculitis prevailing on the buttocks and the posterior surface of the thighs that evolve with subintrant crops of lesions for months and must be distinguished from acute epidemic suppurative folliculitis due to P. aeruginosa and favored by water games. Sterile pustules may persist for months in the palmar-plantar area after scabies. Acrolocated symmetrical micro-pustules can be part of an “ide” reaction to mycosis (1, 2). There are not in the literature localized, recurrent, sterile, self-healing pustules in the site of previous, already cured kerion.